2018
DOI: 10.1016/j.ekir.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib for Reduction of Proteinuria in IgA Nephropathy

Abstract: IntroductionIgA nephropathy is the most common glomerulonephritis in the world. We conducted a pilot trial (NCT01103778) to test the effect of bortezomib in patients with IgA nephropathy and significant proteinuria.MethodsWe treated 8 consecutive subjects from July 2011 until March 2016 with 4 doses of bortezomib. All subjects had biopsy-proven IgA nephropathy and proteinuria of greater than 1 g per day. They were given 4 doses of bortezomib i.v. at 1.3 mg/m2 of body surface area per dose. Changes in proteinur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Previous GWAS has identified PSMB8 and PSMB9 as the susceptibility genes of IgAN, and PSMB9 was found to upregulate in the epidermis of SLE patients (Kiryluk et al, 2012;Nakamura et al, 2016). The proteasome inhibitor bortezomib was effective for the remission of LN and reducing the proteinuria in patients with IgAN (Alexander et al, 2015;Hartono et al, 2018), supporting our results that blue module is involved in the common pathogenesis of IgAN and LN via immunity pathways. In addition, the tubule-specific pink module was broadly downregulated in both diseases and enriched for death pathway.…”
Section: Discussionsupporting
confidence: 89%
“…Previous GWAS has identified PSMB8 and PSMB9 as the susceptibility genes of IgAN, and PSMB9 was found to upregulate in the epidermis of SLE patients (Kiryluk et al, 2012;Nakamura et al, 2016). The proteasome inhibitor bortezomib was effective for the remission of LN and reducing the proteinuria in patients with IgAN (Alexander et al, 2015;Hartono et al, 2018), supporting our results that blue module is involved in the common pathogenesis of IgAN and LN via immunity pathways. In addition, the tubule-specific pink module was broadly downregulated in both diseases and enriched for death pathway.…”
Section: Discussionsupporting
confidence: 89%
“…Different to rituximab in other autoimmune disease, B-cell depletion in IgA nephropathy, which has been suggested to be an autoimmune disease, did not show expected efficacy [14]. In comparison, after a 1-year follow-up in the trial, of all 8 subjects, 3 subjects (38%) had complete remission with proteinuria less than 300 mg per day [15]. The evidence suggests that the (immuno) proteasome may play an important role in IgAN.…”
Section: Ivyspringmentioning
confidence: 77%
“…Notably, several interesting trials testing the effect of proteasome inhibitor in patients with IgAN and significant proteinuria have been performed [15,59]. The outcomes of a single-center open-label pilot trial showed the potential of therapy targeted at (immuno) proteasome in IgAN treatment.…”
Section: The Immunoproteasome As a Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortezomib is a proteasome inhibitor known to target plasma cells. Short term use of bortezomib in select cases of IgAN has demonstrated promising ramifications in reducing proteinuria 154 . A similar unexpected efficiency of rituximab could also be observed in patients with lupus nephritis 155 .…”
Section: Therapeutic Strategies With An Updated Pathophysiological Pementioning
confidence: 99%